2021
DOI: 10.2106/jbjs.rvw.20.00198
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Total Knee Arthroplasty

Abstract: Conversion total knee arthroplasty (TKA) represents a heterogeneous group of procedures and most commonly includes TKA performed after ligamentous reconstruction, periarticular open reduction and internal fixation (ORIF), high tibial osteotomy (HTO), and unicompartmental knee arthroplasty (UKA).» Relative to patients undergoing primary TKA, patients undergoing conversion TKA often have longer operative times and higher surgical complexity, which may translate into higher postoperative complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…One of the challenges is the presence of previous skin incisions, which differ in position and length according to the type of osteotomy and the implant used for fixation [ 33 , 34 ]. The surgeon should determine beforehand if the same incision will be incorporated in the TKA surgical approach or if a different incision will be used; if the latter is the case, at least 6 cm of skin bridge should be considered for optimum healing [ 34 , 35 ]. All knees in the current series were operated through a medial parapatellar approach, incorporating the same HTO incision in 60.6% of the knees; however, in 39.4%, a separate skin incision was required, as the original incision was located laterally for LWCHTO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the challenges is the presence of previous skin incisions, which differ in position and length according to the type of osteotomy and the implant used for fixation [ 33 , 34 ]. The surgeon should determine beforehand if the same incision will be incorporated in the TKA surgical approach or if a different incision will be used; if the latter is the case, at least 6 cm of skin bridge should be considered for optimum healing [ 34 , 35 ]. All knees in the current series were operated through a medial parapatellar approach, incorporating the same HTO incision in 60.6% of the knees; however, in 39.4%, a separate skin incision was required, as the original incision was located laterally for LWCHTO.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue is the need to perform extensile approaches, as difficulty while mobilizing or everting the patella could be encountered [ 34 , 36 ]. To avoid the undue risk of patellar tendon avulsion, the surgeon might consider using a more extensile approach, like performing TTO or a rectus snip [ 35 ]. Hevesi et al [ 32 ] reported that they tend to use the safest approach possible, considering whether hardware removal is needed at the same setting and whether this will be achieved through the same approach for TKA or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, prior to 2020, conversion of either a static or articulating antibiotic spacer to a revision TKA following PJI treatment was coded as CPT 27447. Given the dramatically different outcomes of conversion TKA [9][10][11][12][13][14] and 2-stage exchange for PJI treatment 15,16 relative to a standard primary TKA, one can see why it is important to properly define a study cohort. If the cohort is solely defined by a single CPT code such as 27447, then substantial misclassification bias could be introduced.…”
Section: Pitfallsmentioning
confidence: 99%